Axio-creative Experience of Education at Preschool Institutions of Russia in the 20s–30s of the 20th Century (the Republic of Tatarstan Example) - Mardashova, Ramziya S.; Sadykova, Lilia R.; Hazratova, Firyuza V. (Journal of History Culture and Art Research, 2019)
Based on a comprehensive study of socio-historical, psychological and pedagogical theories and concepts of preschool education, this article puts forward the idea of pedagogical axio-creation, expressed in the system of measures aimed at the creation and formation of new social and moral values in younger generations or at the restoration, rethinking of the old ones. The work is devoted to the consideration of axio-creative experience in the education of preschoolers at the formation stage of the system of public preschool education in Russia in the 20s–30s of the 20thcentury. The study is based on historical material on upbringing children at preschool institutions of the Republic of Tatarstan, which was and is a part of the Russian Federation. The authors of the article focus their attention on solving the tasks of social, moral, ideological and political education of preschoolers. In the course of their investigation there are disclosed and described peculiarities of carrying out pedagogical work on the formation of new social and moral concepts and behavior habits of children. The article reveals and describes the features of labor, patriotic, international and anti-religious education of preschoolers during the studied period. At the same time, the authors consider issues of changing the content of education and upbringing of children in kindergartens, as well as promotion and application of new forms and methods of work with children of preschool age according to the principle of education common to the whole Soviet educational system – connection with life and modernity.